PELATIHAN PEMBUATAN KERIPIK BIJI DURIAN DI DESA ETI, KECAMATAN SERAM BARAT, KABUPATEN SERAM BAGIAN BARAT, PROVINSI MALUKU - Grace Sipahelut, Sophia; Batuwael, Tusye (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
Maluku has a productive prospect in producing durian fruit. In the durian season, durian seed waste is very abundant and has not been widely used, on the other hand, durian seeds have good nutritional content for the body. This service activity aims to introduce the technology of processing durian seed waste into chips to the people of Eti Village, West Seram District, West Seram Regency. The target of this activity is Eti Village community. Activities are carried out in the form of: (1) counseling; (2) training; and (3) program evaluation. The results of the community service programs that have been carried out are 1) Aspects of applying science and technology: this activity is effective in building community independence in utilizing local potential, namely durian seed waste to be processed into processed products; 2) Benefit aspect: increasing people's knowledge and skills in processing durian seeds into chips so as to provide added value and use value to durian seeds. The enthusiasm of the participants in participating in this activity is also very good, which can be seen from the enthusiasm of the participants in participating in this activity from beginning to end.